Artificial intelligence in cardiology: fundamentals and applications. Issue 6 (31st May 2022) - Watson, Xavier; D'Souza, Joshua; Cooper, Daniel; Markham, Ryan
Abstract: Artificial intelligence (AI) is an overarching term that encompasses a set of computational approaches that are trained through generalised learning to autonomously execute specific tasks. AI is a rapidly expanding field in medicine. In particular cardiology, with its high reliance on numerical patient data in decision making, has great potential to benefit from AI. Types of AI, including neural networks and computer vision, can dramatically change the day‐to‐day workflow of cardiologists, primarily through integration in diagnostic imaging modalities, periprocedural planning, electronic health record analysis and patient monitoring. Healthcare systems will undoubtedly become more automated and shift to more AI‐driven methods to improve efficiency and reduce cost. Patients in the end will benefit from these changes with improved diagnostic accuracy, better tailored treatments resulting in a greater quality and quantity of life. In this article, we will describe some of the fundamental principles underlying AI that physicians should have an understanding of, along with current clinical applications.